Oralidade e argumentação : uma proposta de abordagem do gênero debate de opinião - Gama, Débora Cunha Costa (2018)
This research investigates the importance of addressing argumentative oral genres in the classroom, specifically the opinion debate, a gender that aims to discuss a controversial issue among interlocutors, to develop the oral and to increase argumentative capacity. The work was developed in three stages: in the first one was made a survey of the theoretical and bibliographic referentials; in the second stage, data collection was carried out throughout the analysis of part of a didactic material selected through the National Program of Didactic Book (PNLD), precisely the Português: Linguagens collection, by linguists Willian Roberto Cereja and Thereza Cochar Magalhães (2015). The third stage consisted in the elaboration of a didactic sequence of the genre approach and its respective application in pedagogical workshops in a 9th year of elementary education class, in a school of the Municipal Network of Education of Euclides da Cunha – BA, as well as in the analysis of the results of this intervention proposal from the transcribed productions. In a volume apart from this dissertation we present a Teacher's Pedagogical Notebook, as well as some specific material for the student, namely, two theoretical-practical notebooks, for better appropriation of the gender and argumentative techniques. In order to support our discussions, we use Bakhtin conceptions of discursive genres (2003), the socio-theoretical perspective of genres of Bazerman (2009); Marcuschi (2001) and Marcuschi and Dionísio (2007). In this paper, we present the results of the study of the oral and written genres of Dolz, Schneuwly and collaborators (2004). As for the aspects of the argumentation, we use Fiorin conceptions (2016); Perelman and Tyteca theory of argument (2014); the processes of construction of oral argumentation in the context of Ribeiro (2009) and Marques (2011).